PENANGANAN ANAK PELAKU TINDAK PIDANA NARKOTIKA DI KEPOLISIAN RESORT KOTA BESAR MEDAN - ADLIN MUKHTAR TAMBUNAN; Mangasa Manurung Manurung (JURNAL PROINTEGRITA, 2018)
The purpose of this study is to find out and understand the factors that cause of the children to commit narcotics crime, the treatment for children who commit narcotics crime, the obstacles in the treatment for the children who commit narcotics crime in the jurisdiction of police in the big city Resortt of Medan. Data collection in this study was carried out by literature review, namely by collecting data and various reading sources, namely books, magazines, opinions of experts regulations about factors that cause children to commit narcotics crimeimplementation of the investigation of children who commit narcotics crime in the police of big city Resortt of Medan, obstacles in investigating children who commit narcotics crime in the police of big city Resortt of Medan, field research, namely by conducting direct research in the field, in this case the author conducted a study in the police of big city Resortt of Medan and other agencies that respect child protection, using oral interview techniques. The results show that the factors that cause a child to commit narcotics crime are a family situation that is broken home, lack of attention and time given to children, both in the field of education and in maintaining intimacy in the family,fragility of family values or norms, including knowledge of politeness values, a family economy that is unable to support life's needs, including the need to continue school or find work, to prove the courage to take dangerous actions such as speeding, fighting, hanging out with women, to challenge or fight an authority (parents, teachers, law).The investigation of children who committed narcotics crime in the police of big city Resortt of Medan was carried out by investigators, both from the police of Medan. Investigation of a person suspected of being a perpetrator of narcotics abuse was carried out as a follow-up on: reports or complaints, press releases or being caught red handed. Obstacles in the investigation of children who commit narcotics crime in the police of Big City Resortt of Medan are in addition to the organizational Polri needs to increase individual professionalism or individuals in providing services such us abuse of power, use of forcego beyond authority and discrimination, leave requests for services or help or law enforcment without the right reasons, discration that goes beyond the limits and stalling, arrogant, disrespectful, sluggish and has not treated elderly people, children and women appropriatly.